2022
DOI: 10.1177/15271544221076524
|View full text |Cite
|
Sign up to set email alerts
|

Results of a National Survey: Ongoing Barriers to APRN Practice in the United States

Abstract: Limited information is available on the barriers to practice for advanced practice registered nurses (APRNs) among states with full, restricted, and reduced practice. The purpose of this study is to identify practice barriers in relationship to United States (U.S.) state practice authority, APRN type, area of practice (rural, suburban, urban), and nature of practice (outpatient, inpatient, and both). An electronic survey of a convenience sample of APRNs was conducted to assess barriers to practice. Identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The formal practice agreement remained a requirement for 75% of NPs almost 2 years after the initial executive order. Others have also found that formal practice agreements and lack of hospital admitting privileges are the most common NP practice restrictions, which continue to persist despite permanent FPA (Schorn et al, 2022). Required physician signature on hospice/home health orders was most affected in our survey, which was likely a reflection of the federal 2020 CARES Act, rather than the state policy change to FPA.…”
Section: Discussionmentioning
confidence: 99%
“…The formal practice agreement remained a requirement for 75% of NPs almost 2 years after the initial executive order. Others have also found that formal practice agreements and lack of hospital admitting privileges are the most common NP practice restrictions, which continue to persist despite permanent FPA (Schorn et al, 2022). Required physician signature on hospice/home health orders was most affected in our survey, which was likely a reflection of the federal 2020 CARES Act, rather than the state policy change to FPA.…”
Section: Discussionmentioning
confidence: 99%
“…These practices interfere with the ability of APRNs to provide patient care follow-up, limit patients’ choice of providers, and limit APRNs’ visibility in care ( Poghosyan et al, 2013 ; Anen & McElroy, 2015 ). Nonregulatory barriers may vary by practice or geographically within a single state as well as among states ( Schorn et al, 2022 ).…”
Section: Aprn Practice Barriersmentioning
confidence: 99%
“…Regulatory barriers are those that are determined through federal or state laws, regulations, statutes, and policies 16 . Examples include the requirement for physician supervision or limitation of the types of services an APRN can provide 15 . Organizational and institutional policies comprise nonregulatory barriers 16 and can vary by facility or practice within a state.…”
Section: Barriers For Aprnsmentioning
confidence: 99%
“…A variety of barriers continue to limit APRNs, including CNSs, from practicing to the highest level of their education and training. 15 Regulatory barriers are those that are determined through federal or state laws, regulations, statutes, and policies. 16 Examples include the requirement for physician supervision or limitation of the types of services an APRN can provide.…”
Section: Barriers For Aprnsmentioning
confidence: 99%